Utilization of multiple spinal cord stimulation (SCS) waveforms in chronic pain patients. (3rd August 2017) - Berg, Anthony P; Mekel-Bobrov, Nitzan; Goldberg, Edward; Huynh, Dat; Jain, Roshini
ABSTRACT: Background : Advances in spinal cord stimulation (SCS) have improved patient outcomes, leading to its increased utilization for chronic pain. Chronic pain is dynamic showing exacerbations, variable severity, and evolving pain patterns. Given this complexity, SCS systems that provide a broad range of stimulation waveforms may be valuable. Methods : The aim of this research was to characterize the usage pattern of stimulation waveforms and field shapes in chronic pain patients implanted with the Spectra System. A review of daily device usage in a cohort of 250 patients implanted for a minimum duration of one month was conducted. Results : With follow-ups ranging between 1 month and 1 year post-implant, 72.8% of patients used Standard Rate, 34.8% Anode Intensification, 23.2% Higher Rate, and 8.4% Burst stimulation waveforms. Collectively, 60% used 1 or more advanced waveforms, either exclusively or along with Standard Rate. A trend showed patients continuing to use up to 3 programs one year post-implant. Conclusion : When given a choice, SCS patients often utilize a variety of waveforms, suggesting that patients may benefit from a single system that provides multiple waveforms and field shapes to customize therapy and improve efficacy.